The Effect of Simulating Climbing Movements on Rock Memory and Exploratory Movement in Rock Climbing. Issue 3 (June 2022) - Sugi, Takahiro; Nițu, Anda-Maria; Ishihara, Masami
Simulating climbing movements on a given route is important for fluent rock climbing. We investigated the effect of simulated action during rock climbing route finding on memory and exploratory movement. Participants were 12 climbers and 12 non-climbers who completed three experimental tasks: (a) a questionnaire, the Vividness of Movement Imagery Questionnaire-2 (VMIQ-2) for measuring vividness of motor imagery, (b) a memory task requiring recognition of rock climbing holds on the route, and (c) a traversing task requiring participants to climb a given route and count the number of exploratory movements made during climbing. During route finding in the memory/traversing task, we experimentally manipulated the simulative body action with motor imagery. Results showed that the simulative action affected exploratory movement during climbing, but it did not affect memorization of the holds. In the traversing task, climbers showed more exploratory movement when the simulative action was present during route finding, while the non-climbers showed an opposite trend. Moreover, for non-climbers, the effect of the simulative action was modulated by the vividness of kinesthetic imagery. We concluded that simulative body action during route finding facilitated motor imagery and spatial information processing for subsequent climbing involving exploratory movement.